2008
DOI: 10.1590/s0066-782x2008000600004
|View full text |Cite
|
Sign up to set email alerts
|

Mortalidade precoce por doenças cardiovasculares e desigualdades sociais em Porto Alegre: da evidência à ação

Abstract: SummaryBackground: Two perspectives, the economic (disease causing impoverishment) and social (poverty causing illness), have internationally disputed the justification for public health policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
16

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 20 publications
1
15
0
16
Order By: Relevance
“…Bassanesi et al 19 observed that almost half the mortality from CVD before 65 years can be attributed to poverty. Ishitani et al 20 emphasized the importance of education in the inverse relationship between CVD mortality and socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Bassanesi et al 19 observed that almost half the mortality from CVD before 65 years can be attributed to poverty. Ishitani et al 20 emphasized the importance of education in the inverse relationship between CVD mortality and socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Em São Paulo, uma investigação verificou que o risco de morte por infarto do miocárdio em homens aumentou 100% na área mais pobre da cidade, quando comparada às áreas mais ricas 19 . Pesquisa realizada em Porto Alegre concluiu que quase a metade da mortalidade por doenças cardiovasculares antes dos 65 anos associou-se a pobreza 20 . Outro trabalho, conduzido para verificar a mortalidade por doenças cardiovasculares e níveis socioeconômicos em São José do Rio Preto, São Paulo, evidenciou que as áreas com populações com pior nível socioeconômico apresentaram maior coeficiente de mortalidade 21 .…”
Section: Discussionunclassified
“…La hipertensión arterial sistémica -HAS es considerada como un problema de salud pública tanto por presentar alta prevalencia como también por ser un factor de riesgo para diversas otras patologías, principalmente para las enfermedades cardiovasculares, que son las principales causas de mortalidad en todo el mundo, inclusive en grupos poblacionales de condiciones socioeconómicas desfavorables [1][2][3] . En 2000, aproximadamente el 26% de la población adulta en todo el mundo ya presentaba HAS y esta proporción deberá aumentar para el 29% hasta el año de 2025, si no llevar a cabo medidas de intervención.…”
Section: Introductionunclassified